Adhesive tape capable of losing adhesive force after being electrified and preparation process of adhesive tape

By using a specific ratio of acrylic copolymers and pyridine-modified reduced graphene oxide in the energized de-adhesion tape, a multi-linked network is formed, which solves the problems of slow response and poor stability of existing energized de-adhesion tapes and achieves a fast and stable energized de-adhesion effect.

CN121006167APending Publication Date: 2025-11-25TAICANG JIN YU ELECTRONICS MATERIALS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511276031.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing de-adhesive tapes have problems such as excessively long response time, high voltage requirements, high energy consumption, high operational risks, and insufficient stability during the disassembly of electrical components, especially the unstable de-adhesive effect under extreme temperatures.

Method used

Using acrylic copolymers in specific mass ratios as the adhesive matrix, a host-guest inclusion complex is formed by combining pyridine-modified reduced graphene oxide, hydroxypropyl-β-cyclodextrin, and 1-(2-aminoethyl)ferrocene. Through the combination of multiple cross-linking networks and thermosensitive polymers, the conductivity and electro-response performance are enhanced, ensuring the sensitivity and stability of de-adhesion upon energization.

Benefits of technology

It achieves rapid response, low voltage requirements, and high stability in the de-adhesion tape when powered on, with minimal decrease in peel force after multiple uses, and stable de-adhesion effect adaptable to different ambient temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121006167A_ABST
    Figure CN121006167A_ABST
Patent Text Reader

Abstract

The invention relates to a power-on adhesive tape capable of losing adhesion and a preparation process thereof. The power-on adhesive tape comprises a base film, a conductive layer and an adhesive layer, the adhesive layer is prepared from the following raw materials in parts by mass: 40 to 50 parts of acrylate copolymer, 3 to 5 parts of terpene resin, 0.2 to 0.5 part of initiator, 20 to 30 parts of solvent, 3 to 5 parts of pyridine modified reduced graphene oxide, 8 to 10 parts of hydroxypropyl-beta-cyclodextrin, 2.0 to 2.4 parts of 1-(2-aminoethyl) ferrocene and 4 to 5 parts of polyethylene glycol diacrylate. The component A is prepared from the following components in parts by weight: 0.5 to 0.8 part of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.2 to 0.5 part of benzotriazole antioxidant and 1 to 2 parts of polycarbodiimide; the raw materials of the acrylate copolymer comprise a soft monomer and a hard monomer in a mass ratio of (2.5-3.5): 1. The power-on viscosity-loss adhesive tape is high in peel strength and high in power-on viscosity-loss sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to an adhesive tape, and more specifically, to an electrically conductive non-adhesive tape and its preparation process. Background Technology

[0002] In scenarios involving the temporary fixing and disassembly of electronic components, the temporary bonding of electrical components such as smart logistics labels or packaging requiring electrothermal triggering, and heat-removable medical patches or sensors, electrically conductive non-adhesive tapes have gained widespread attention due to their ability to regulate adhesive force through electrical signals. Existing technologies for temporary fixing mainly include tapes based on principles such as electroinduced ion migration and electroinduced phase transition.

[0003] However, existing technologies have many drawbacks. For example, tapes based on the principle of ion migration have slow ion migration speeds, resulting in excessively long unadhesion response times and affecting the disassembly efficiency of electrical components. Tapes using electro-phase change materials have difficult-to-control phase change temperatures, are easily affected by ambient temperature, and exhibit unstable unadhesion effects at extreme temperatures. Conductive polymer composite tapes have limited substrate deformation, often requiring higher voltages and longer energizing times to achieve effective unadhesion, increasing energy consumption and operational risks, and potentially damaging high-precision electrical components. Some researchers have attempted to provide more sensitive conductivity by incorporating conductive hydrogels into tapes; however, the conductive stability of hydrogels is insufficient, and their "water-based characteristics" and "structural sensitivity" limit their durability, environmental adaptability, peel strength, and functional stability.

[0004] Therefore, providing a novel electrically conductive non-adhesive tape with rapid non-adhesion response, low voltage requirements, and stable performance has significant practical application value. Summary of the Invention

[0005] In order to obtain a current-sensitive and stable current-sensitive adhesive tape, this application provides a current-sensitive adhesive tape and its preparation process.

[0006] In a first aspect, this application provides an electrically conductive non-adhesive tape, comprising a base film, a conductive layer, and an adhesive layer. The adhesive layer comprises the following raw materials in parts by weight: 40-50 parts of acrylate copolymer, 3-5 parts of terpene resin, 0.2-0.5 parts of initiator, 20-30 parts of solvent, 3-5 parts of pyridine-modified reduced graphene oxide, 8-10 parts of hydroxypropyl-β-cyclodextrin, 2.0-2.4 parts of 1-(2-aminoethyl)ferrocene, 4-5 parts of polyethylene glycol diacrylate, 0.5-0.8 parts of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.2-0.5 parts of benzotriazole antioxidant, and 1-2 parts of polycarbodiimide. The acrylate copolymer comprises soft monomers and hard monomers in a mass ratio of (2.5-3.5):1.

[0007] By adopting the above scheme, when a certain mass ratio of soft monomers and hard monomers acrylonitrile copolymers is used as the adhesive matrix to provide basic adhesion, the resulting adhesive copolymer exhibits strong intermolecular polar forces, creep resistance, and adjustable crosslinking density, avoiding a significant increase in Tg. This results in tapes that are both responsive and leave minimal residue during use. Furthermore, by forming a host-guest inclusion complex with the temperature-sensitive hydrophobic cavity inside hydroxypropyl-β-cyclodextrin and the Fc group of 1-(2-aminoethyl)ferrocene, the inclusion complex dissociates at high temperatures. This, combined with the redox properties of Fc, imparts responsiveness to detack upon energization. Simultaneously, better fixation may occur due to hydrogen bonds formed by the -CH2CH2NH2 segment on the outside of the cavity or electrostatic attraction with the pyridine group. Upon energization, the oxidized Fc... + Because of its positive charge, the repulsive force with the hydrophobic cavity increases, and the hydrogen bond anchoring effect of the amino group can accelerate Fc. + The resulting tape, extracted from the cavity, exhibits high sensitivity to loss of adhesion upon electrical conduction, while the amino groups are anchored to the cross-linking network, inhibiting Fc. + Migration loss and the fact that Fc is not easily released from cyclodextrin, leading to response decay, allow the tape to maintain high peel strength and electrical sensitivity even after repeated use. Adding a certain amount of reduced graphene oxide enhances conductivity; the layered structure also bridges the components. Pyridine modification, forming ion pairs with the copolymer carboxyl groups and coordinating with Fc, accelerates electron transfer, enhancing the electrochemical activity of the system and giving the product better electroresponsive performance and higher electrical de-adhesion sensitivity. Adding a certain amount of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer further stabilizes the system. Adding a certain amount of benzotriazole protects long-term stability. Adding a certain amount of polycarbodiimide assists crosslinking and simultaneously captures carboxylic acids generated from trace amounts of moisture in the system, further improving the long-term electrical de-adhesion stability of the tape.

[0008] In one specific feasible implementation, the preparation process of pyridine-modified reduced graphene oxide includes: dispersing reduced graphene oxide in ethanol, ultrasonic treatment, adding 4-mercaptopyridine, heating under nitrogen protection and reflux reaction, centrifugation, washing, and vacuum drying.

[0009] By adopting the above scheme, the reaction steps are relatively simple, and the -SH group of 4-mercaptopyridine reacts with the sp groups of the reduced graphene oxide surface defect sites. 2 Carbon undergoes nucleophilic addition, and the resulting pyridine ring enhances the interfacial bonding force with the six-membered ring of reduced graphene oxide through π-π interactions, resulting in high energization sensitivity.

[0010] In one specific feasible implementation, the reduced graphene oxide sheet diameter is 0.5-7.5 μm.

[0011] By adopting the above scheme, the reduced graphene oxide sheet size can achieve a better bridging effect, forming ion pairs with the carboxyl groups of the copolymer and accelerating electron transfer together with the π-π interaction with Fc, resulting in a tape with higher electrical sensitivity.

[0012] In one specific feasible implementation, the pyridine-modified reduced graphene oxide is PNIPAM-AA grafted pyridine-modified reduced graphene oxide. The preparation process includes: ultrasonically dispersing the pyridine-modified reduced graphene oxide in tetrahydrofuran, adding N-isopropylacrylamide, acrylic acid, and azobisisobutyronitrile, heating and stirring to react, centrifuging and washing, and vacuum drying to obtain PNIPAM-AA grafted pyridine-modified reduced graphene oxide.

[0013] By adopting the above scheme, the temperature-sensitive polymer PNIPAM is grafted, which undergoes a hydrophilic-hydrophobic conformational change before and after the low critical dissolution temperature. It swells below the critical dissolution temperature and shrinks hydrophobically above the LCST, which drives the movement of reduced graphene oxide to improve conductivity. The resulting tape has a more uniform and stable electrical response.

[0014] Simultaneously, it is possible that after being energized and heated, the modified and reduced graphene oxide is surrounded by a hydrophobic microenvironment due to the contraction of PNIPAM, which compresses the surrounding space and "squeezes out" the hydrophilic Fc. + Leaving the hydrophobic cavity, and Fc + It exhibits strong repulsion from hydrophobic environments, further promoting the migration of Fc to hydrophilic regions such as polyethylene glycol segments within the system, thus accelerating the process. + The sensitivity of the resulting tape was further improved by increasing the extraction rate from the cavity.

[0015] In one specific feasible implementation, the number-average molecular weight of polyethylene glycol diacrylate is 700-1000.

[0016] By adopting the above approach, the acrylate groups at both ends of the polyethylene glycol diacrylate segments can participate more effectively in polymerization, further optimizing the crosslinking network and allowing small molecule Fc to participate more efficiently. + The system exhibits good stability during diffusion, while its hydrophilicity prevents the aggregation of HP-β-cyclodextrin, ensuring its uniform distribution and effective inclusion of Fc. Upon energization, it provides diffusion channels, accelerating the diffusion of Fc. + It is extracted from the HP-β-cyclodextrin cavity.

[0017] In one specific feasible implementation, the mass ratio of PNIPAM-AA grafted pyridine modified reduced graphene oxide, hydroxypropyl-β-cyclodextrin, and 1-(2-aminoethyl)ferrocene is (3.8-4.2):(8.8-9.2):2.2.

[0018] By adopting the above approach, the effect of the temperature-sensitive polymer on the adhesive system is suitable for Fc. + The tape prepared by the encapsulation and decapsulation process of HP-β-cyclodextrin cavity has high sensitivity and good reusability.

[0019] In one specific feasible implementation, the mass ratio of acrylate-butyl acrylate-acrylonitrile copolymer and polyethylene glycol diacrylate is (9-12):1.

[0020] By adopting the above scheme, the cross-linked network within the prepared tape is more rational, and a certain amount of hydrophilic polyethylene glycol segments are evenly distributed. After energizing, Fc + It is easier to get out.

[0021] In one specific feasible implementation, the mass ratio of soft monomers to hard monomers is (2.8-3.2):1, and the soft monomers include isooctyl acrylate and butyl acrylate, while the hard monomers include methyl methacrylate and styrene.

[0022] By adopting the above scheme, the distribution of crosslinking points was adjusted, and the distribution of soft and hard segments was more suitable for the use of the tape prepared in this application. The resulting tape has better sensitivity and reusability.

[0023] In one specific feasible implementation, hydroxypropyl-β-cyclodextrin is HDI-grafted hydroxypropyl-β-cyclodextrin.

[0024] By adopting the above approach, the -NCO group is grafted onto the hydroxyl group of HP-β-cyclodextrin, while the other end of the -NCO group remains free or reacts with the polymer matrix. This provides an "anchor point" for connection with the polymer matrix, firmly anchoring the cyclodextrin within the polymer network, thus making hydroxypropyl-β-cyclodextrin more stable in the system.

[0025] Secondly, this application provides a process for preparing an electrically conductive non-adhesive tape, comprising the following steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to an aqueous ethanol solution according to the mass fractions, dispersed evenly, and then centrifuged and freeze-dried to obtain the inclusion complex. S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 200-300 rpm for 10-12 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat and mix them evenly to obtain an adhesive solution, then add the premix and continue mixing at 400-600 rpm for 15-20 minutes, degas under vacuum to obtain the adhesive layer raw material; S4: Composite the base film and the conductive layer, then coat the adhesive layer material onto one side of the conductive layer, preheat to evaporate the solvent, and cure by step temperature increase to obtain an electrically conductive non-adhesive tape.

[0026] By adopting the above technical solution, the preparation process is simple, the resulting tape has a reasonable multi-crosslinked network structure, high electrical sensitivity, and low peel force reduction after multiple bonding.

[0027] In summary, this application has the following beneficial effects: This application utilizes acrylic acid-butyl acrylate-acrylonitrile copolymer as the base component of the tape, combined with a multi-crosslinked network, featuring a combination of soft-hard segments and hydrophobic-hydrophilic segments, to produce a tape with high stability and Fc. + The encapsulation and release from the cavity of hydroxypropyl-β-cyclodextrin are relatively smooth, resulting in a highly sensitive de-adhesion effect on the prepared electro-adhesion tape, while also exhibiting relatively stable performance with repeated use.

[0028] This application improves electron transfer efficiency by modifying reduced graphene oxide with pyridine, which combines ion pairing and π-π stacking. Further grafting PNIPAM-AA further enhances electron transport efficiency by making the reduced graphene oxide stack more compact, and the resulting hydrophilic / hydrophobic changes accelerate the flow rate (Fc). + The movement of the tape makes it more sensitive to electrical conductivity and loss of adhesion. Attached Figure Description

[0029] Figure 1 Schematic diagram of the structure of an adhesive tape that loses its adhesion when powered.

[0030] Explanation of reference numerals in the attached figures: 1. Adhesive layer; 2. Aluminum foil; 3. Base membrane. Detailed Implementation

[0031] To further aid in understanding the technical solution of the present invention, several specific implementation examples are provided below to describe the technical solution of the present invention in more detail. All of these described embodiments are only some embodiments of the present invention, and not all of them. The following specific embodiments can be combined with each other. The same or similar concepts or processes may not be described again in some embodiments. Unless otherwise specified, the reaction devices, monomer compounds and other materials involved in the following embodiments are commercially available.

[0032] The benzotriazole antioxidant was UV-326; polyethylene glycol diacrylate with a weight average molecular weight of 400 was purchased from Bailingwei Technology (J&K193525), polyethylene glycol diacrylate with a weight average molecular weight of 700 was purchased from Wuhan Xinxinjiali Biotechnology Co., Ltd. (26570489), and polyethylene glycol diacrylate with a weight average molecular weight of 2000 was purchased from Xi'an Qiyue Biotechnology; 0.5-3μm reduced graphene oxide was purchased from Muke Nano MK2005.

[0033] The following examples are further illustrations of the present invention, but the present invention is not limited thereto.

[0034] Preparation Example Preparation Example 1: Isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer 200g of isooctyl acrylate, 100g of butyl acrylate, 50g of methyl methacrylate and 50g of styrene were mixed evenly and stirred at 75°C for 5 hours. After cooling, an acrylic copolymer was obtained.

[0035] Preparation Example 2: Isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer 100g isooctyl acrylate, 50g butyl acrylate, 100g methyl methacrylate and 100g styrene were mixed evenly and stirred at 75°C for 5 hours. After cooling, an acrylic copolymer was obtained.

[0036] Preparation Example 3: Butyl acrylate-methyl methacrylate-styrene copolymer 300g of butyl acrylate, 50g of methyl methacrylate and 50g of styrene were mixed evenly and stirred at 75°C for 5 hours. After cooling, an acrylic copolymer was obtained.

[0037] Preparation Example 4: Pyridine-modified reduced graphene oxide 5g of reduced graphene oxide was dispersed in 120ml of ethanol and sonicated at 500W for 1 hour until uniformly suspended. 3g of 4-mercaptopyridine was added and the mixture was refluxed at 80℃ for 24h under nitrogen protection. After centrifugation, the mixture was washed three times with ethanol and dried under vacuum at 60℃ to obtain pyridine-modified reduced graphene oxide.

[0038] Preparation Example 5: PNIPAM-AA Grafted Pyridine Modified Reduced Graphene Oxide Pyridine-modified reduced graphene oxide was ultrasonically dispersed in tetrahydrofuran, and N-isopropylacrylamide, acrylic acid, and azobisisobutyronitrile were added. The mixture was heated and stirred, centrifuged and washed, and then vacuum dried to obtain PNIPAM-AA grafted pyridine-modified reduced graphene oxide.

[0039] Preparation Example 6: HDI-grafted hydroxypropyl-β-cyclodextrin 20g of hydroxypropyl-β-cyclodextrin was dissolved in 150ml of DMF at 80℃ and stirred for 30 minutes under nitrogen protection. The temperature was then lowered to 65℃, and a mixture of 7g of hexamethylene diisocyanate (HDI) and 0.1g of dibutyltin dilaurate was added dropwise. After 1 hour, the temperature was raised to 80℃ and reacted for 2.5 hours to obtain HDI-grafted hydroxypropyl-β-cyclodextrin. Example

[0040] Example 1 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer prepared in Preparation Example 1, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of pyridine-modified reduced graphene oxide prepared in Preparation Example 4, 8g of hydroxypropyl-β-cyclodextrin, 2.2g of 1-(2-aminoethyl)ferrocene, 4.5g of polyethylene glycol diacrylate with a weight average molecular weight of 700, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70 ml of 15 wt% ethanol aqueous solution according to their mass, stirred at 60 °C for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0041] Example 2 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer obtained in Preparation Example 2, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of pyridine-modified reduced graphene oxide obtained in Preparation Example 4, 8g of hydroxypropyl-β-cyclodextrin, 2.2g of 1-(2-aminoethyl)ferrocene, 4.5g of polyethylene glycol diacrylate with a weight average molecular weight of 700, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70 ml of 15 wt% ethanol aqueous solution according to their mass, stirred at 60 °C for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0042] Example 3 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of pyridine-modified reduced graphene oxide, 8g of hydroxypropyl-β-cyclodextrin, 2.2g of 1-(2-aminoethyl)ferrocene, 4.5g of polyethylene glycol diacrylate with a weight average molecular weight of 700, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70 ml of 15 wt% ethanol aqueous solution according to their mass, stirred at 60 °C for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0043] Example 4 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer obtained in Preparation Example 3, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of PNIPAM-AA grafted pyridine modified reduced graphene oxide obtained in Preparation Example 5, 8g of hydroxypropyl-β-cyclodextrin, 2.2g of 1-(2-aminoethyl)ferrocene, 4.5g of polyethylene glycol diacrylate with a weight average molecular weight of 700, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70 ml of 15 wt% ethanol aqueous solution according to their mass, stirred at 60 °C for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0044] Example 5 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer obtained in Preparation Example 3, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of PNIPAM-AA grafted pyridine modified reduced graphene oxide obtained in Preparation Example 5, 9g of hydroxypropyl-β-cyclodextrin, 2.2g of 1-(2-aminoethyl)ferrocene, 4.5g of polyethylene glycol diacrylate with a weight average molecular weight of 700, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70 ml of 15 wt% ethanol aqueous solution according to their mass, stirred at 60 °C for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0045] Example 6 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of PNIPAM-AA grafted pyridine modified reduced graphene oxide, prepared in Preparation Example 5, 9g of HDI grafted hydroxypropyl-β-cyclodextrin, 2.2g of 1-(2-aminoethyl)ferrocene, 4.5g of polyethylene glycol diacrylate with a weight average molecular weight of 700, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide, prepared in Preparation Example 6; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70 ml of 15 wt% ethanol aqueous solution according to their mass, stirred at 60 °C for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0046] Example 7 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of PNIPAM-AA grafted pyridine modified reduced graphene oxide, prepared in Preparation Example 5, 9g of HDI grafted hydroxypropyl-β-cyclodextrin, 2.2g of 1-(2-aminoethyl)ferrocene, 4.5g of polyethylene glycol diacrylate with a weight average molecular weight of 400, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide, prepared in Preparation Example 6; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70 ml of 15 wt% ethanol aqueous solution according to their mass, stirred at 60 °C for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0047] Example 8 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of PNIPAM-AA grafted pyridine modified reduced graphene oxide, prepared in Preparation Example 5, 9g of HDI grafted hydroxypropyl-β-cyclodextrin, 2.2g of 1-(2-aminoethyl)ferrocene, 4.5g of polyethylene glycol diacrylate with a weight average molecular weight of 2000, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide, prepared in Preparation Example 6; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70 ml of 15 wt% ethanol aqueous solution according to their mass, stirred at 60 °C for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0048] Example 9 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of PNIPAM-AA grafted pyridine modified reduced graphene oxide, prepared in Preparation Example 5, 9g of HDI grafted hydroxypropyl-β-cyclodextrin, 2.2g of 1-(2-aminoethyl)ferrocene, 5.5g of polyethylene glycol diacrylate with a weight average molecular weight of 2000, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide, prepared in Preparation Example 6; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70 ml of 15 wt% ethanol aqueous solution according to their mass, stirred at 60 °C for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0049] Comparative Example Comparative Example 1 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of reduced graphene oxide, 8g of hydroxypropyl-β-cyclodextrin, 2.2g of 1-(2-aminoethyl)ferrocene, 4.5g of polyethylene glycol diacrylate with a weight average molecular weight of 700, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide, prepared in Example 1; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70ml of 15wt% ethanol aqueous solution according to their mass, stirred at 60℃ for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0050] Comparative Example 2 Raw material quality: 45g of isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer, 4g of terpene resin, 0.4g of azobisisobutyronitrile, 25g of ethyl acetate, 4g of reduced graphene oxide, 8g of hydroxypropyl-β-cyclodextrin, 2.2g of Fc, 4.5g of polyethylene glycol diacrylate with a weight average molecular weight of 700, 0.6g of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.3g of benzotriazole antioxidant UV-326, and 1.5g of polycarbodiimide obtained in Preparation Example 1; Preparation steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to 70 ml of 15 wt% ethanol aqueous solution according to their mass, stirred at 60 °C for 6 hours, and then centrifuged and freeze-dried to obtain the inclusion complex; S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 300 rpm for 10 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat to 80℃ and mix evenly to obtain the adhesive solution, then add the premix and continue mixing at 400 rpm for 15 minutes, ultrasonically disperse at 40 kHz for 10 minutes, and degas under vacuum to obtain the adhesive layer raw material. S4: Coat the acrylate pressure-sensitive adhesive onto the PET base film, then laminate it with aluminum foil, cure at 60°C for 5 minutes, coat the adhesive layer material onto one side of the aluminum foil, preheat at 80°C for 10 minutes, raise the temperature to 90°C for 1 hour, then at 110°C for 20 minutes, and then attach the release film to one side of the adhesive layer to obtain the electrically conductive non-adhesive tape.

[0051] Performance testing test 1: Referring to the standard "GB / T 2792-2014 Test method for peel strength of adhesive tape", the prepared non-adhesive tape was tested before being energized: After removing the release film from the prepared tape, it was adhered to a steel plate and pressed with a 2kg rubber roller for 3 back and forth strokes. After being placed at 23℃ for 24 hours, the test was conducted and recorded as the peel force F at 180° before being energized.

[0052] Then, the peel force test after energization was performed: the release film of the new energized non-adhesive tape was removed, it was attached to the steel plate, pressed back and forth 3 times with a 2kg rubber roller, and placed at 23℃ for 24 hours. One end of the electrode was clamped on the steel plate and the other end was clamped on the aluminum foil for peeling. The attached sample was subjected to an energization treatment of 10V×30s, and then the peel force at 180° was tested and recorded as the peel force F1 after energization.

[0053] Test 2: The sample from Test 1 that was electrified was reattached to a new steel plate. A 2kg rubber roller was used to press it back and forth three times. The process of peeling was repeated with and without electricity, three times in total. After being placed at 23℃ for 24 hours, the peel force after re-attachment was tested and recorded as F2. The recovery ratio was calculated as follows: Recovery Ratio = (F2 / F1) × 100%.

[0054] Test 3: The minimum loss of tack condition was tested in the following test: After removing the release film from the newly made tape, it was adhered to a steel plate and pressed back and forth three times with a 2kg rubber roller. After being placed at 23℃ for 24 hours, an energized loss of tack test was conducted at 10V. The tape was peeled 180° with a peeling force of 0.5N / 25mm, and the energized time required for complete peeling was recorded.

[0055] The test results are summarized in Table 1.

[0056] Table 1 In conjunction with Examples 1-3, 9, Comparative Examples 1-2, and Table 1, this application utilizes a certain mass ratio of soft and hard monomers to obtain an isooctyl acrylate-butyl acrylate-methyl methacrylate-styrene copolymer, and combines it with a certain mass ratio of polyethylene glycol diacrylate and terpene resin as the matrix resin. The resulting tape exhibits a reasonable distribution of soft and hard segments and good dynamic reversibility. The addition of a certain mass ratio of pyridine-modified reduced graphene oxide provides coordination and complexation capabilities, thereby improving the tape's sensitivity to tack loss during electrical conduction.

[0057] In conjunction with Examples 1, 4-5 and Table 1, this application further grafts PNIPAM-AA onto pyridine-modified reduced graphene oxide, and limits the mass ratio of PNIPAM-AA grafted with pyridine-modified reduced graphene oxide, hydroxypropyl-β-cyclodextrin, and 1-(2-aminoethyl)ferrocene. This causes the reduced graphene oxide to contract and move after being heated by energization, thereby improving conductivity and "extruding" Fc. + Leaving the cavity further enhances the sensitivity of the resulting tape.

[0058] In conjunction with Examples 1 and 7-8 and Table 1, this application, by limiting the weight-average molecular weight of polyethylene glycol diacrylate, not only optimizes the crosslinking network but also makes the diffusion channels more compatible with Fc. + Particle size further accelerates Fc while reducing overall structural aging damage to the tape. + The release effect results in a more sensitive tape.

[0059] This application and its specific embodiments are merely explanations of this application and are not intended to limit it. After reading this specification, those skilled in the art can make modifications to these embodiments without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A type of electrically conductive non-adhesive tape, characterized in that: The material includes a base film, a conductive layer, and an adhesive layer. The adhesive layer comprises the following raw materials in parts by weight: 40-50 parts of acrylate copolymer, 3-5 parts of terpene resin, 0.2-0.5 parts of initiator, 20-30 parts of solvent, 3-5 parts of pyridine-modified reduced graphene oxide, 8-10 parts of hydroxypropyl-β-cyclodextrin, 2.0-2.4 parts of 1-(2-aminoethyl)ferrocene, 4-5 parts of polyethylene glycol diacrylate, 0.5-0.8 parts of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 0.2-0.5 parts of benzotriazole antioxidant, and 1-2 parts of polycarbodiimide. The acrylate copolymer comprises soft monomers and hard monomers in a mass ratio of (2.5-3.5):

1.

2. The electrically conductive non-adhesive tape according to claim 1, characterized in that: The preparation process of the pyridine-modified reduced graphene oxide includes: dispersing the reduced graphene oxide in ethanol, ultrasonic treatment, adding 4-mercaptopyridine, heating and refluxing under nitrogen protection, centrifugation, washing, and vacuum drying.

3. The electrically conductive non-adhesive tape according to claim 1, characterized in that: The reduced graphene oxide has a sheet diameter of 0.5-7.5 μm.

4. The electrically conductive non-adhesive tape according to claim 1, characterized in that: The pyridine-modified reduced graphene oxide is PNIPAM-AA grafted pyridine-modified reduced graphene oxide. The preparation process includes: ultrasonically dispersing pyridine-modified reduced graphene oxide in tetrahydrofuran, adding N-isopropylacrylamide, acrylic acid, and azobisisobutyronitrile, heating and stirring to react, centrifuging and washing, and vacuum drying to obtain PNIPAM-AA grafted pyridine-modified reduced graphene oxide.

5. The electrically conductive non-adhesive tape according to claim 1, characterized in that: The number-average molecular weight of the polyethylene glycol diacrylate is 700-1000.

6. The electrically conductive non-adhesive tape according to claim 4, characterized in that: The mass ratio of PNIPAM-AA grafted pyridine modified reduced graphene oxide, hydroxypropyl-β-cyclodextrin, and 1-(2-aminoethyl)ferrocene is (3.8-4.2):(8.8-9.2):2.

2.

7. The electrically conductive non-adhesive tape according to claim 1, characterized in that: The mass ratio of the acrylic acid-butyl acrylate-acrylonitrile copolymer and polyethylene glycol diacrylate is (9-12):

1.

8. The electrically conductive non-adhesive tape according to claim 1, characterized in that: The mass ratio of the soft monomer to the hard monomer is (2.8-3.2):

1. The soft monomer includes isooctyl acrylate and butyl acrylate, and the hard monomer includes methyl methacrylate and styrene.

9. The electrically conductive non-adhesive tape according to claim 1, characterized in that: The hydroxypropyl-β-cyclodextrin is HDI-grafted hydroxypropyl-β-cyclodextrin.

10. A process for preparing an electrically conductive non-adhesive tape according to any one of claims 1-9, characterized in that, Includes the following steps: S1: Hydroxypropyl-β-cyclodextrin and 1-(2-aminoethyl)ferrocene were added to an aqueous ethanol solution according to the mass fractions, dispersed evenly, and then centrifuged and freeze-dried to obtain the inclusion complex. S2: The inclusion complex, pyridine-modified reduced graphene oxide, and polyethylene glycol diacrylate were premixed at 200-300 rpm for 10-12 minutes to obtain a premix. S3: Weigh the remaining components by mass, heat and mix them evenly to obtain an adhesive solution, then add the premix and continue mixing at 400-600 rpm for 15-20 minutes, degas under vacuum to obtain the adhesive layer raw material; S4: Composite the base film and the conductive layer, then coat the adhesive layer material onto one side of the conductive layer, preheat to evaporate the solvent, and cure by step temperature increase to obtain an electrically conductive non-adhesive tape.

Citation Information

Cited By

  • Electrolytic adhesive, electrolytic cotton adhesive tape and preparation method

    CN121495492A